Targeting the YB-1/PD-L1 Axis to Enhance Chemotherapy and Antitumor Immunity - Tao, Zhen; Ruan, Hailong; Sun, Lin; Kuang, Dong; Song, Yongchun; Wang, Qi; Wang, Tao; Hao, Yi; Chen, Ke (Cancer immunology research, 2019)
Tumor cells can escape immune destruction in tumor chemoresistance, but the mechanism for this phenomenon remains unclear. Y-box binding protein 1 (YB-1), which is upregulated in chemoresistant tumor cells, plays a role in the acquisition of multidrug resistance. Here, we demonstrate that chemotherapy induced an immunosuppressive microenvironment in the tumor and induced immune evasion through YB-1-mediated programmed death-1 ligand 1 (PD-L1) upregulation. Examination of the YB-1 protein and mRNA showed an increase in YB-1 expression in hepatocellular carcinoma (HCC). High YB-1 expression negatively correlated with the overall survival of HCC patients. YB-1 expression positively correlated with PD-L1, and YB-1 induced PD-L1 expression by binding a PD-L1 promoter motif. YB-1 expression was upregulated in chemoresistant HCC cells, and YB-1 knockdown reversed chemoresistance via T-cell activation in the tumor microenvironment due to blocked PD-L1 expression. We also found that inhibition of the tumor immunosuppressive environment and immune evasion was accompanied by proliferation of functional cytotoxic CD8 T cells and inhibition of myeloid-derived suppressor cells and regulatory T cells in the tumor environment. Our data indicate that targeting the YB-1 signaling axis, which simultaneously reverses both tumor immune evasion and multidrug resistance, may improve the antitumor response. This finding suggests a treatment modality against tumor chemoresistance.